2008
DOI: 10.1080/03610730802070282
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Artificial Ceroid/Lipofuscin from Different Tissue Materials of Rats

Abstract: The artificial ceroid/lipofuscin pigments originated from different organ tissues, including liver, brain, heart, and kidney of rats, and biomaterials were studied with improved fluorometric techniques. With all tissue materials exposed under ultraviolet (UV) light, a series of similar fluorescent colors were observed under microfluorometer. Analogous fluorescence spectra were also demonstrated with a three-dimensional (3-D) front-surface fluorometric technique despite of the tissue differences. Measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the current study, immunocytochemistry for oxidized lipids revealed their presence within macrophages, located in structures that morphologically resemble lipofuscin. This is not surprising, since lipofuscin appears to contain non-digestible remnants of oxidized cellular components, accumulating in macrophages or resident cells of the CNS, for instance neurons (Keller et al , 2004; Wang et al , 2008). Similarly, nitrosylated epitopes, recognized by antibodies against nitrotyrosine, were mainly seen in macrophages (Cross et al , 1998; Liu et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, immunocytochemistry for oxidized lipids revealed their presence within macrophages, located in structures that morphologically resemble lipofuscin. This is not surprising, since lipofuscin appears to contain non-digestible remnants of oxidized cellular components, accumulating in macrophages or resident cells of the CNS, for instance neurons (Keller et al , 2004; Wang et al , 2008). Similarly, nitrosylated epitopes, recognized by antibodies against nitrotyrosine, were mainly seen in macrophages (Cross et al , 1998; Liu et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence showed that peroxidative damage to lipid and protein occurs with the aging process and that the products of these reactions accumulate with age [2, 27, 28, 50, 51]. Aging rats treated with E2 reversed the MDA levels to almost normal levels in the liver, suggesting its anti-lipidperoxidative abilities [8, 49].…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the lipofuscin-like lipopigments as peroxidized products of lipids and other intracellular macromolecules was supported by later investigations, even leading to their proposal as AF biomarkers of oxidative damages induced in livers with lipid accumulation and oxidative stress. 87 , 127 , 173 , 174 Actually, an increasing number of endogenous fluorophores has been considered for comprehensive AF based diagnostic applications in hepatology, depending on the complex biochemical composition characterizing the liver tissue due to its engagement in several metabolic and detoxificating functions. 84-87 , 175 In addition to NAD(P)H, flavins and lipofuscins, the overall liver tissue AF emission can originate from proteins, vitamin A and fatty acids likely playing a role as interconnected autofluorescent biomarkers of liver disorders.…”
Section: Miscellanea Of Endogenous Fluorophores In Liver Disorders Amentioning
confidence: 99%